2017
DOI: 10.1515/sues-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Socially Responsible Organizational Culture

Abstract: While scholarly literature abounds with research on organizational culture and CSR, this study adds knowledge to the field, redefining a new concept: that of socially responsible organizational culture. In our opinion, socially responsible organizational culture encompasses all the values, beliefs, norms and strategies that facilitate, direct, operate and develop the relations between organization and stakeholders in order to harmonize these relationships and increase economic, social and environmental perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The t-statistic value was 3.236 and the p value was 0.001, which indicated that organizational culture had a significant influence on competitive advantage, so H2 in this study was accepted. This significance was in line with research by Daniel and Ellen (1999), Linnenluecke and Griffiths (2010), Sharma and Sharma (2010), Valencia et al (2011), Ganescu and Gangone (2017). Innovative organizational cultures oriented towards the organization's vision and mission are the organization's competitive advantage, which shape the character of the organization.…”
Section: Hypothesissupporting
confidence: 85%
See 2 more Smart Citations
“…The t-statistic value was 3.236 and the p value was 0.001, which indicated that organizational culture had a significant influence on competitive advantage, so H2 in this study was accepted. This significance was in line with research by Daniel and Ellen (1999), Linnenluecke and Griffiths (2010), Sharma and Sharma (2010), Valencia et al (2011), Ganescu and Gangone (2017). Innovative organizational cultures oriented towards the organization's vision and mission are the organization's competitive advantage, which shape the character of the organization.…”
Section: Hypothesissupporting
confidence: 85%
“…Based on the research that has been done above related to the relationship between social capital and competitive advantage, the following hypothesis was constructed: HI: Social capital had a significant effect on competitive advantage in the industrial sector of chemical manufacturing 3.4.2. Relationship of organizational culture to competitive advantage Ganescu and Gangone (2017) found in their research that organizational culture and social responsibility influence corporate excellence and improve economic performance, while Sharma and Sharma (2010) stated that organizational culture and the development of organizational transformation strategies had a positive impact on competitive advantage that impacted textile companies in India in long term. The results of research conducted by Valencia et al (2011) found that organizational culture was a stimulant to the company's innovative capabilities, one which had a significant impact on the competitive advantage of companies, especially important for innovation capabilities rather than imitating similar companies, in order to be superior and a pioneer in the market.…”
Section: Relationship Of Social Capital To Competitive Advantagementioning
confidence: 99%
See 1 more Smart Citation
“…However, many organizations with values appear to be more inclined toward socially responsible behaviors. Socially responsible organizational culture includes values, beliefs, norms and strategies that nurture stakeholder relationships to achieve ideal economic, social and environmental performances (Ganescu and Gangone, 2017). Aguilera et al (2004) classified CSR motivations according to three levels: instrumental, which focuses on the need for control; relational, which prioritizes organizations' need for belongingness; and moral, which focuses on the need of the organization to have a meaningful existence in society.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the perspective of [20], CSR is a tool to implement stakeholder theory. In the study on the implementation of CSR of EU member states, scholars found that enterprises that can implement CSR well have better performance [21]. From the perspective of consumers as a stakeholder, when a CSR is consistent with the consumers' moral foundations, and the enterprise persistently adheres to the CSR, consumers will show positive responses to the enterprise, such as gaining consumers' word-of-mouth and loyalty [22,23].…”
Section: Corporate Social Responsibility and Stakeholder Theorymentioning
confidence: 99%